Variable Carbon Source Utilization, Stress Resistance, and Virulence Profiles Among Listeria monocytogenes Strains Responsible for Listeriosis Outbreaks in Switzerland - Muchaamba, Francis; Eshwar, Athmanya K.; Stevens, Marc J. A.; von Ah, Ueli; Tasara, Taurai (Frontiers in Microbiology, 2019)
A combination of phenotype microarrays, targeted stress resistance and virulence assays and comparative genome analysis was used to compare a set of L. monocytogenes strains including those involved in previous Swiss foodborne listeriosis outbreaks. Despite being highly syntenic in gene content these strains showed significant phenotypic variation in utilization of different C-sources as well as in resistance of osmotic and pH stress conditions that are relevant to host and food associated environments. An outbreak strain from the 2005 Swiss Tomme cheese listeriosis outbreak (Lm3163) showed the highest versatility in C-sources utilized whereas the strain responsible for the 1983 to 1987 Vacherin Montd’or cheese listeriosis outbreak (LL195) showed the highest tolerance to both osmotic and pH stress conditions among the examined strains. Inclusion of L-norvaline led to enhanced resistance of acidic stress in all the examined strains and there were strain-strain specific differences observed in the ability of other amino acids and urea to enhance acid stress resistance in L. monocytogenes. A strain dependent inhibition pattern was also observed upon inclusion of β-phenylethylamine under alkaline stress conditions. In targeted phenotypic analysis the strain-specific differences in salt stress tolerance uncovered in phenotypic microarrays were corroborated and variations in host cell invasion and virulence among the examined strains were also revealed. Outbreak associated strains representing lineage I serotype 4b showed superior pathogenicity in a zebrafish infection model whilst Lm3163 a lineage II serotype 1/2a outbreak strain demonstrated the highest cellular invasion capacity amongst the tested strains. A genome wide sequence comparison of the strains only revealed few genetic differences between the strains suggesting that variations in gene regulation and expression are largely responsible for the phenotypic differences revealed among the examined strains. Our results have generated data that provides a potential basis for the future design of improved Listeria specific media to enhance routine detection and isolation of this pathogen as well as provide knowledge for developing novel methods for its control in food.